Effectual excavation of weathered rocks using geological features - Mohamad, Edy Tonnizam (Institute of Quarrying Malaysia, 2010)
In the tropical region where the occurrence of a thick profile of weathered zone is common, ripping is always accepted as the limit of mechanical breaking before blasting works is opted. However, the nature of rock and its weathering profile play a very significant role in evaluating the excavation assessment. Many issues have emerged in ripping work for sedimentary area where the occurrence of bedding, foliation and the inhomogeniety of rock can greatly influence the excavatability of the weathered rocks. This chapter aims to highlight some of the problems that arise in weathered sedimentary areas and as what have been experienced during the implementation of surface excavation works.